Topotactic desolvation and condensation reactions of 3D Zn3TiF7(H2O)2(taz)3·S (S = 3H2O or C2H5OH). Issue 48 (26th November 2020) - Albino, M.; Lhoste, J.; Body, M.; Legein, C.; Hémon-Ribaud, A.; Maisonneuve, V.; Leblanc, M.
Abstract : Thermodiffraction, IR, DFT calculations, and 1 H and 19 F NMR characterizations of the desolvatation and reversible condensation reactions of Zn3 TiF7 (taz)3 family. Abstract : Crystals of two new 3D hybrid compounds, trans -Zn3 TiF7 (H2 O)2 (taz)3 ·3H2 O and cis -Zn3 TiF7 (H2 O)2 (taz)3 ·C2 H5 OH, have been obtained by solvothermal synthesis ((taz) − = 1, 2, 4-triazolate C2 H2 N3 ligand). Their structures, determined from X-ray single crystal diffraction data in Cm and Pnma space groups, respectively, are based on Zn3 N9 (H2 O)2 F3 trimers linked by TiF6 octahedra that build trans - or cis -chains ∞ [Zn3 TiN9 (H2 O)2 F7 ]. Water or ethanol in the structure cavities is released below 110 °C to give trans - or cis -Zn3 TiF7 (H2 O)2 (taz)3 and, on further heating, these intermediate phases dehydrate and lead to anhydrous trans - or cis -Zn3 TiF7 (taz)3 . At 110 °C, the loss of ethanol concerns only ≈1/3 of the weight of cis -Zn3 TiF7 (H2 O)2 (taz)3 ·C2 H5 OH while the remaining part subsists up to 180 °C. This behaviour is attributed to a core–shell type configuration. Rehydration in humid air occurs at room temperature for the anhydrous cis -phase. All desolvated, dehydrated or rehydrated phase structures have been determined by X-ray powder diffraction and ab initio Rietveld refinements. All transformations from solvated or hydrated to anhydrous phases are realised without any symmetry change and the trans or cis connection of the TiF6 octahedra is maintained together with the overall features of the 3D networks. The final loss of water molecules induces a condensation reaction that implies the connection of the trimers by fluorine atoms; the structures of the anhydrous phases Zn3 TiF7 (taz)3 are then described by Zn3 N9 F4 trimers. 1 H and 19 F MAS NMR studies, coupled with DFT calculations of NMR parameters, confirm the water loss and support the strutural models while evidencing both the positional disorders, more likely of the organic parts, and the F motions within TiF6 octahedra.